KELEKATAN ANTARA ANAK DENGAN ORANG TUA DAN REGULASI DIRI DENGAN HUBUNGAN SOSIAL ANAK USIA DINI KELAS III SD - RAHMATUNNISA, SRIYANTI (PPs UNJ, 2012)
The purpose of this study was to obtain an overview of attachment between parents and children with self-regulation by social relationships in early childhood grade III Elementary School, Village Elementary School in Pondok Bambu, East Jakarta, in 2011. This study uses quantitative methods to the correlational approach. The study population is a third-grade students. Study sample of 56 students chosen at random sampling. The data was collected using a questionnaire-shaped instrument. The results showed that the viscosity (X1) and self-regulation (X2), either individually or jointly have a positive relationship with social skills (Y). The conclusion of this study is that the attachment between parent and child self-regulation, made a significant contribution to social relations. The study provides recommendations to the parents to establish attachment to the child so as to present themselves before the child as someone who can be imitated in an attempt to develop self-regulation skills that eventually the child can adjust to the rules and norms that apply generally, so as to establish social relationships fine.Keywords: Attachment, Self regulation, Social relationships